Oncogenic Ras is downregulated by ARHI and induces autophagy by Ras/AKT/mTOR pathway in glioblastoma - Chen Zhong; Mengting Shu; Junyi Ye; Xiaoxiong Wang; Xin Chen; Zhendong Liu; Wenyang Zhao; Boxian Zhao; Zhixing Zheng; Zhiqin Yin; Ming Gao; Haiqi Zhao; et al. (BMC Cancer, 2019)
Abstract Background Glioblastoma is a disease with high heterogeneity that has long been difficult for doctors to identify and treat. ARHI is a remarkable tumor suppressor gene in human ovarian cancer and many other cancers. We found over-expression of ARHI can also inhibit cancer cell proliferation, decrease tumorigenicity, and induce autophagic cell death in human glioma and inhibition of the late stage of autophagy can further enhance the antitumor effect of ARHI through inducing apoptosis in vitro or vivo. Methods Using MTT assay to detect cell viability. The colony formation assay was used to measure single cell clonogenicity. Autophagy associated morphological changes were tested by transmission electron microscopy. Flow cytometry and TUNEL staining were used to measure the apoptosis rate. Autophagy inhibitor chloroquine (CQ) was used to study the effects of inhibition at late stage of autophagy on ARHI-induced autophagy and apoptosis. Protein expression were detected by Western blot, immunofluorescence and immunohistochemical analyses. LN229-derived xenografts were established to observe the effect of ARHI in vivo. Results ARHI induced autophagic death in glioma cells, and blocking late-stage autophagy markedly enhanced the antiproliferative activites of ARHI. In our research, we observed the inhibition of RAS-AKT-mTOR signaling in ARHI-glioma cells and blockade of autophagy flux at late stage by CQ enhanced the cytotoxicity of ARHI, caused accumulation of autophagic vacuoles and robust apoptosis. As a result, the inhibition of RAS augmented autophagy of glioma cells. Conclusion ARHI may also be a functional tumor suppressor in glioma. And chloroquine (CQ) used as an auxiliary medicine in glioma chemotherapy can enhance the antitumor effect of ARHI, and this study provides a novel mechanistic basis and strategy for glioma therapy.